2018
DOI: 10.24873/j.rpemd.2018.06.217
|View full text |Cite
|
Sign up to set email alerts
|

Oral health behaviors and dental caries in a sample of portuguese militaries

Abstract: To determine the prevalence of dental caries and oral health behaviors in a sample of the Portuguese army. Methods: An observational cross-sectional study was conducted in a sample of army soldiers of the Infantry Regiment no. 14 of Viseu, Portugal, using a questionnaire. The study involved 122 members of the armed forces, who were asked to complete a questionnaire autonomously. The questionnaire enquired about general oral-health behaviors but focused mainly on: i) frequency of toothbrushing, ii) use of denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Regarding the oral hygiene index observed in the sample, it was found that 19% did not present dental plaque in the intraoral observation (Value 0), 30.6% had “Value 1”, 32% “Value 2” and 18.4% “Value 3”. A study carried out on a sample of Portuguese individuals also obtained similar results with 16.4% of the sample without plaque (Value 0), 20.5% “Value 1”, 58.2% “Value 2” and 4.9% “Value 3” [ 24 ]. In both studies, “Value 2”, which corresponds to the presence of visible plaque, was the most prevalent.…”
Section: Discussionmentioning
confidence: 60%
“…Regarding the oral hygiene index observed in the sample, it was found that 19% did not present dental plaque in the intraoral observation (Value 0), 30.6% had “Value 1”, 32% “Value 2” and 18.4% “Value 3”. A study carried out on a sample of Portuguese individuals also obtained similar results with 16.4% of the sample without plaque (Value 0), 20.5% “Value 1”, 58.2% “Value 2” and 4.9% “Value 3” [ 24 ]. In both studies, “Value 2”, which corresponds to the presence of visible plaque, was the most prevalent.…”
Section: Discussionmentioning
confidence: 60%
“…En cuanto al índice de higiene bucal observado en la muestra, se encontró que el 19% no presentó placa (valor cero), el 30,6% tuvo "valor uno", el 32% "valor dos" y el 18,4% "valor tres". También un estudio realizado en una muestra de la población portuguesa (55) obtuvieron resultados similares con un 16,4% de la muestra sin placa (valor cero), un 20,5%…”
Section: íNdice De Placa Silness Y Loeunclassified